When can we trust population thresholds in regression discontinuity designs? - Florian Ade; Ronny Freier (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
A recent literature has used variation just around deterministic legislative population thresholds to identify the causal effects of institutional changes. This paper reviews the use of regression discontinuity designs using such population thresholds. Our concern involves three arguments: (1) simultaneous exogenous (co-)treatment, (2) simultaneous endogenous choices and (3) manipulation and precise control over population measures. Revisiting the study by Egger and Koethenbuerger (2010), who analyse the relationship between council size and government spending, we present new evidence that these three concerns do matter for causal analysis. Our results suggest that empirical designs using population thresholds are only to be used with utmost care and confidence in the precise institutional setting.
Keywords: C2; D7; H7; 330; regression discontinuity design; population thresholds; local elections; government spending; Bevölkerungsentwicklung; Regression; Kommunalwahl; Öffentliche Ausgaben; Bevölkerungsdichte